MISALIGNMENT CHALLENGES IN TEACHING ENGLISH AT ELEMENTARY SCHOOL LEVEL - Rinduani Putri Ayu; Machdalena Vianty (Universitas Lambung Mangkurat, 2025)
This study explores the challenges faced by the alumni of Pendidikan Profesi Guru (PPG) Prajabatan or Pre-Service Teacher Profession Education Program in teaching English at the elementary school level. Using a qualitative approach, data were collected from three alumni through written interviews and analyzed thematically. The study identified four main challenges in implementing English teaching at the elementary level: (1) a mismatch between curriculum content and students’ proficiency levels, (2) limited structured listening input and learning aids, (3) misalignment between curriculum design and classroom realities, and (4) insufficient teacher autonomy to adapt materials for linguistic and cultural relevance. These results highlight the need for curriculum adjustments to support English teaching at the elementary level, including context-specific training and resource provision. This study contributes to improving teacher education policies that are more adaptive and grounded in real classroom needs.